The role of marketing in environmental protection - Dudás, Katalin (Marketing & Menedzsment, 2019)
Achieving sustainable development is unimaginable only with the contribution of international organisations, governments, civil and business organizations; to solve ecological problems require individuals’ efforts too. The unsustainable buyer, consumer and user patterns have to be changed; environmentally friendly activities and way of thinking have to be promoted. Marketing has the most extensive theoretical and practical knowledge in connection with consumption, consumer behaviour and promoting new things. Thus, making radical changes in existing consumer patterns needs some important marketing tasks. For example, we have to define the environmentally conscious consumer segments; we need to disclose the influencing factors of environmentally friendly activities for the sake of a more successful promotion of any manifestation of environmental consciousness.